KESENJANGAN DISTRIBUSI TENAGA KESEHATAN DI PUSKESMAS WILAYAH INDONESIA TIMUR (Analisis Data IFLS East 2012) - Nurul Hikmah B.; Lutfan Lazuardi; Dwi Handono (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Since 1980s the Ministry of Health has used several approaches to determine staffing needs, using projections based on public health status, demographic changes and health programs that exist. This study describes the distribution of health personnel gap in eastern Indonesia due to see the injustice of health workers in eastern Indonesia so that the government can deal seriously and firmly to the problems of the distribution of health personnel, particularly areas that are difficult to reach. Purpose: This study aims to determine the unequal distribution of health personnel in the health centers in Eastern Indonesia. Methods: This study is a quantitative research with quantitative methods using cross sectional design. Using a large-scale secondary data from the Indonesia Family Life Survey (IFLS) East. Results: This study indicate that there is a big gap in equity of health workforce in primary health care in eastern Indonesia experienced vacancies even some of primary health care both doctors, nurses, midwives and midwife. This is evident from the distribution of health personnel imbalance between primary care located in areas with high and low number of population; high and low poverty rates; geographic location based on the urban/rural and remoteness even provinces. Conclusion: Primary health care in eastern Indonesia more experienced vacancies in particular labor of doctors and midwives, as well as the low number of community health workers to prove that primary health care is oriented on promotive and preventive neglected. Optimizing the role of government as a regulator and facilitator to give more focus and help the areas that lack health worker especially in the province of East Nusa Tenggara, Maluku and West Papua are more likely to be a shortage of public health vacancy even doctors and midwives.